Tingkat Kecemasan Anak Usia Sekolah Pasca Bencana Gempa Bumi - Erviana Erviana; Ismar Ismar; Masniati Masniati (KOLONI, 2023)
Earthquakes have always been shown to be linked to mental health problems, such as anxiety and post-traumatic stress disorder. A survey shows that after a disaster event around 15-20% of the population will experience mild or moderate mental disorders. Earthquakes have consistently been shown to be associated with mental health problems such as anxiety, depression and post-traumatic stress disorder in the immediate aftermath of disasters. This condition will get worse if it is not detected early and handled properly, thus requiring mental health services (trauma healing). Excessive anxiety can have a detrimental effect on the mind and body and can even lead to physical ailments. The purpose of this study was to determine the anxiety level of post-earthquake school-age children in Taan Village, Tapalang District, Mamuju Regency. Method, this study uses a quantitative descriptive method. The population of this study were school-age children in Taan Village, Tapalang District, Mamuju Regency. Results In this study, it was found that most school-age children experienced mild anxiety (45.5%), normal anxiety (6.1%) moderate anxiety (30.3%) severe anxiety (18.2%). Conclusion: This study shows that most school-age children experience mild anxiety after the earthquake in Taan Village, Tapalang District, Mamuju Regency. Keywords: Earthquake, Anxiety, School Aged Children